The mechanism of painful diabetic neuropathy in streptozotocin-induced sprague dawley rats following treatment with l-alpha-aminoadipate or U0126 drug - Haris, Khalilah (2025)
Painful diabetic neuropathy (PDN) is a complication of diabetes mellitus (DM). This chronic neuropathic pain treatment is challenging due to limited options and less effective therapeutics. This study aimed to explore the mechanism of PDN by investigating how L-α-aminoadipate (LAA-astrocytes inhibitor drug) and U0126 (ERK inhibitor drug) affect the expression of protein and mRNA of astrocytes, extracellular signal-regulated kinase (ERK), Downstream regulatory element antagonist modulator (DREAM) and Brain-derived neurotrophic factor (BDNF) in the spinal cord of streptozotocin-induced PDN rats, specifically Type 1 DM (T1DM). One hundred twenty-six Sprague-Dawley male rats were assigned to 6 groups (n=21 per group) consisting of normal control group (C), PDN-diabetic control group (PDN), PDN+LAA treated groups: L100 (low dose) and L200 (high dose) and PDN+U0126 treated groups: U5 (low dose) and U10 (high dose). T1DM was induced with a single intraperitoneal injection of streptozotocin at 60 mg/kg. The pain behavioural assessment was performed by Von Frey test, hot plate test and formalin test to determine tactile allodynia (Day 0, 14 and 22), thermal hyperalgesia (Day 0, 14 and 22) and chemical hyperalgesia (Day 23). Two (2) weeks period was allowed for all DM rats to develop PDN condition and was determined based on tactile allodynia by Von Frey test results on Day 14. Then, treatment of either saline, LAA (100 nmol/day or 200 nmol/day) or U0126 (5 µg/day or 10 µg/day) was administered intrathecally for seven consecutive days. The rats were sacrificed on Day 26 after the formalin test and the lumbar enlargement region of the spinal cord was collected for Haematoxylin and Eosin (H&E) staining, immunohistochemistry and qPCR analyses. The results showed that PDN group developed tactile allodynia and thermal hyperalgesia by which these symptoms were attenuated in L100, L200, U5 and U10 groups (PDN-treated groups) (p<0.05) on Day 22 whilst attenuation of chemical hyperalgesia was observed in L100 group (Phase 1) and U5 group (Phase 2) only. Meanwhile, H&E analysis revealed a marked gliosis as shown by the morphological changes and accumulation of astrocytes with a decreased histological score of L100 and U5 groups (p<0.05) ipsilaterally and contralaterally when compared with the PDN group. Immunohistochemistry analysis showed that PDN-treated groups signiﬁcantly (p<0.05) attenuated the total number of astrocytes (Glial fibrillary acidic protein (GFAP)), phospho-ERK (phospho-ERK), DREAM and BDNF protein levels when compared to the PDN group. This finding is further supported by qPCR mRNA expression, which demonstrated that GFAP, ERK1, DREAM and BDNF mRNA expression were significantly reduced in all PDN-treated groups (p<0.05). Pearson correlation analysis revealed that there was a significant positive correlation (p<0.05) between protein and mRNA expression level of GFAP (r=0.7882), phosho-ERK (r=0.7321), DREAM (r=0.5166) and BDNF (r=0.5118). In conclusion, the findings suggested that all PDN-treated groups showed attenuation in tactile allodynia, thermal and chemical hyperalgesia, down-regulation of astrocytes, phospho-ERK, DREAM and BDNF of STZ-induced PDN rats following treatment with LAA or U0126 drug through modulating the inhibition of astrocytes-ERK interaction pathways in the pathogenesis of PDN.